Classroom Management: Islamic Religious Education Learning In Bandar Lampung City - Hayati, Santi; Septuri, Septuri; Dermawan, Oki (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to determine planning, analyze organizing, identify implementation, and supervise supervision in learning Islamic religious education in public elementary school 1 Surabaya and public elementary school 2 Sawah Brebes, Bandar Lampung, Indonesia. Qualitative descriptive research method approach, two data components namely primary data and secondary data, data collection techniques with observation, interview and documentation techniques. The validity test uses data triangulation and method triangulation. The subjects of this research are the Principal and Islamic Religious Education Teacher. both schools have good efforts in classroom management in Islamic religious education. However, there are differences in the focus and approach used in the aspects of planning, organizing, implementing, and supervising the class.